2020
DOI: 10.2967/jnumed.119.238477
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping the Amyloid Buildup Curve in Alzheimer Disease? Partial-Volume Effect Correction of Longitudinal Amyloid PET Data

Abstract: It was hypothesized that the brain β-amyloid buildup curve plateaus at an early symptomatic stage of Alzheimer disease (AD). Atrophy-related partial-volume effects (PVEs) degrade signal in hot-spot imaging techniques such as amyloid PET. The current study, a longitudinal analysis of amyloid-sensitive PET data, investigated the effect on the shape of the β-amyloid curve in AD when PVE correction (PVEC) is applied. Methods: We analyzed baseline and 2-y follow-up data for 216 symptomatic individuals on the AD con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Although earlier work indicated that Aβ pathology may reach a plateau during the dementia phase of AD, 47 recent findings suggest that this may not be the case. 48 As such, we were not able to examine the effect of higher Aβ-PET SUVR values on p-tau isoforms but were nonetheless able to identify the significantly higher dynamic range of p-tau217 Lilly using the available Aβ-PET from participants with out dementia. Although we acknowledge the lack of Aβ-PET across all groups as a limitation, very high concordance is seen between CSF Aβ42/Aβ40 and Aβ-PET.…”
Section: Discussionmentioning
confidence: 93%
“…Although earlier work indicated that Aβ pathology may reach a plateau during the dementia phase of AD, 47 recent findings suggest that this may not be the case. 48 As such, we were not able to examine the effect of higher Aβ-PET SUVR values on p-tau isoforms but were nonetheless able to identify the significantly higher dynamic range of p-tau217 Lilly using the available Aβ-PET from participants with out dementia. Although we acknowledge the lack of Aβ-PET across all groups as a limitation, very high concordance is seen between CSF Aβ42/Aβ40 and Aβ-PET.…”
Section: Discussionmentioning
confidence: 93%
“…In this case, PVC substantially improved our flortaucipir-to-NFT correlation, and our laterality scores were more in line with the postmortem counts than without PVC. Previous reports have shown PVC improves detection and longitudinal measurement in real and simulated PET data [ 4 , 55 , 66 ], with one study finding it increased variability for amyloid PET [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…125 Such differences were also observed by Rullman et al, who found a significant effect of PVC on Aβ-positive subjects, but none on Aβ-negative subjects, 126 and a significant positive effect of PVC in MCI and AD groups in another study. 127 These results…”
Section: Dose-reduction Strategiesmentioning
confidence: 71%
“…106,107 Most studies found that PVC increases the change in tracer uptake but also increases the measurement uncertainty. 5,[124][125][126][127] Increases in rates of change due to PVC may affect subjects with higher amyloid more, as suggested by Brendel et al who found a decrease in percentage change over time in healthy controls and MCI subjects, versus an increase in AD subjects. 125 Such differences were also observed by Rullman et al, who found a significant effect of PVC on Aβ-positive subjects, but none on Aβ-negative subjects, 126 and a significant positive effect of PVC in MCI and AD groups in another study.…”
Section: Dose-reduction Strategiesmentioning
confidence: 93%